Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.148
|View full text |Cite
|
Sign up to set email alerts
|

On Max-Clique for intersection graphs of sets and the Hadwiger-Debrunner numbers

Abstract: Let HD d (p, q) denote the minimal size of a transversal that can always be guaranteed for a family of compact convex sets in R d which satisfy the (p, q)-property (p ≥ q ≥ d + 1). In a celebrated proof of the Hadwiger-Debrunner conjecture, Alon and Kleitman proved thatThis paper has two parts. In the first part we present several improved bounds on HD d (p, q). In particular, we obtain the first near tight estimate of HD d (p, q) for an extended range of values of (p, q) since the 1957 Hadwiger-Debrunner theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Since there is no known example of a family of convex sets in R 2 that satisfies the (4, 3)-property for which the piercing number exceeds 3, we make the following conjecture: Over the last few decades extensive research has been done to improve the Alon-Kleitman bounds, see e.g., [20,21,22]. For an excellent survey on the (p, q)-problem we refer the reader to [23].…”
Section: R D -Convex Societiesmentioning
confidence: 99%
“…Since there is no known example of a family of convex sets in R 2 that satisfies the (4, 3)-property for which the piercing number exceeds 3, we make the following conjecture: Over the last few decades extensive research has been done to improve the Alon-Kleitman bounds, see e.g., [20,21,22]. For an excellent survey on the (p, q)-problem we refer the reader to [23].…”
Section: R D -Convex Societiesmentioning
confidence: 99%
“…The combinatorial and geometrical properties of families of sets in Euclidean space has been a thriving area of research in discrete geometry and combinatorics for many decades. It was initiated by the classical theorem of Helly [24], asserting that if F is a family of convex sets in R d in which every d + 1 members have nonempty intersection, then some point lies in every set in F. This landmark result led to the study of covering numbers (also sometimes called piercing numbers or hitting numbers) of families of sets, that is, the minimal number of points needed to "pierce" every set in a family given some local intersection property [5,16,21,29,28]. Helly's theorem is sharp in general, but improved bounds on covering numbers can be obtained if one restricts the convex sets in question.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable result of this kind is by Kleitman et al [7] who showed that HD 2 (4, 3) ≤ 13 (compared to the upper bound of 345 obtained in [1]). Recently, it was shown in [6] that HD d (p, q) ≤ p − q + 2 for all ε > 0, p ≥ p 0 (ε), and q > p…”
Section: Introductionmentioning
confidence: 99%
“…The best currently known upper bound that holds for all q, HD d (p, q) =Õ(p d· q−1 q−d ) (also shown in [6]), is apparently far from being tight.…”
Section: Introductionmentioning
confidence: 99%